Evidence for Dual Binding Sites for 1,1,1-Trichloro-2,2-bis(p-chlorophenyl)ethane (DDT) in Insect Sodium Channels - Du, Yuzhe (J Biol Chem, 2016)
1,1,1-Trichloro-2,2-bis(p-chlorophenyl)ethane (DDT), the first organochlorine insecticide, and pyrethroid insecticides are sodium channel agonists. Although the use of DDT is banned in most of the world due to its detrimental impact on the ecosystem, indoor residual spraying of DDT is still recommended for malaria control in Africa. Development of resistance to DDT and pyrethroids is a serious global obstacle for managing disease vectors. Mapping DDT binding sites is necessary for understanding mechanisms of resistance and modulation of sodium channels by structurally different ligands. The pioneering model of the housefly sodium channel visualized the first receptor for pyrethroids, PyR1, in the II/III domain interface and suggested that DDT binds within PyR1. Previously, we proposed the second pyrethroid receptor, PyR2, at the I/II domain interface. However, whether DDT binds to both pyrethroid receptor sites remains unknown. Here, using computational docking of DDT into the K(v)1.2-based mosquito sodium channel model, we predict that two DDT molecules can bind simultaneously within PyR1 and PyR2. The bulky trichloromethyl group of each DDT molecule fits snugly between four helices in the bent domain interface, whereas two p-chlorophenyl rings extend into two wings of the interface. Model-driven mutagenesis and electrophysiological analysis confirmed these propositions and revealed 10 previously unknown DDT-sensing residues within PyR1 and PyR2. Our study proposes a dual DDT-receptor model and provides a structural background for rational development of new insecticides.